Development of our TAVI protocol for emergency initiation of cardiopulmonary bypass. (January 2015) - Fernandes, P; Cleland, A; Bainbridge, D; Jones, PM; Chu, MWA; Kiaii, B
All transcatheter aortic valve implantation (TAVI) cases are done in our hybrid operating room with a multidisciplinary team and a primed cardiopulmonary bypass (CPB) circuit on pump stand-by. We decided that we would resuscitate all patients undergoing a TAVI procedure via a transfemoral, transapical or transaortic approach, if required. Perfusion plays an essential role in providing rescue CPB for patient salvage when catastrophic complications occur. To coordinate the multidisciplinary effort, we have developed a written safety checklist that assigns a pre-determined role for team members for the rapid sequence initiation of CPB. Although many TAVI patients are not candidates for conventional aortic valve replacements, we feel strongly that rescue CPB should be offered to all TAVI patients to allow the correction of potentially reversible complications. This protocol is included in every surgical "Time Out" involving a TAVI procedure (Figure 1). The protocol has led to rapid and safe CPB initiation in less than five minutes of cardiac arrest. It has also led to a coordinated and consistent team, with pre-specified roles and improved communication. We discuss a case series of four TAVI patients who required emergent use of CPB. The first few cases did not have a written protocol. The experience from these cases led to the development of our protocol. We identified a lack of coordination, wasted movements, unnecessary delayed resuscitation and overall chaos, each of which was targeted for correction with the protocol. We will discuss the merits of the protocol in two recent TAVI cases which required emergent CPB.